"Modelo de planificación para el diseño de proyectos habitacionales sustentables considerando viviendas de interés social” - Granda Arbeláez, Freddy Ernesto (2017)
The residential complexes that are developed in the city of Huaquillas do not consider habitability factors in their design and planning process, so this does not allow the development of sustainable housing projects linked to social housing. This leads to the need to propose a planning model through the comparative analysis of design, normative and sustainability criteria; That allows the design of sustainable housing projects considering housing of social interest, in addition to being able to identify the procedures used in the planning models, to determine the characteristic elements of the sustainable housing projects and to associate sequentially the planning stages with the characteristics of the housing projects Sustainable considering social housing. The applied methodology is based on a qualitative approach, since it is justified in the bibliographic research of journals, articles, theses, etc., according to the objectives set forth; The analysis of real estate projects developed in other sectors of similar characteristics, in addition to considering the criterion of the Municipal GAD of Huaquillas, focused on standards of planning, regulation and legal housing projects. The results obtained from this analysis allow defining variables related to the sustainable system of cities, housing projects, and parameters of sustainability (habitability). Based on the results obtained, the proposal stresses the need to link the stages that shape the development of a housing project (both in the right choice of territory and in the definition of the type of housing solution) with the factors of habitability present in Sustainable systems. Finally, the methodological proposal is constituted by a flow diagram, which defines a planning model for the design of sustainable housing projects, considering the development of social housing.